Cost Effective Submarine Electrophoresis Apparatus - Sundaravel Kumar1, Ranadive Ananth Govindaraju1*, Ashok Ganapathy2, Arun Kumar Meenakshisundaram1 (Journal of Experimental Sciences, 2011)
Electrophoresis is the process of differential movement or migration of ions by attraction or repulsion in an electric field, which has a wide range of application in the field of biological science. In this paper a cost effective electrophoretic apparatus was designed and described, which replaces the conventional platinum electrode with copper and silver electrode. A greater change in PH was observed in cathode side which helps the biological molecule to migrate much faster than in a conventional apparatus. This apparatus was also tested for their effect on plant and animal DNA electrophoresis and compared with the conventional electrophoretic apparatus. Thus the results from our study reveal a cost effective electrophoretic apparatus which do not disturb the migration of biological molecule.